2001
DOI: 10.1001/archotol.127.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-up of Tinnitus Complaints

Abstract: Severe tinnitus shows some signs of improvement over time, especially when psychological treatment has been given. Tinnitus maskability is an important prognostic factor of future tinnitus annoyance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 18 publications
(22 reference statements)
5
59
0
4
Order By: Relevance
“…In previous clinical trials with the MML as the efficacy outcome variable, such a relationship has indeed been observed [Jastreboff et al, 1994;Davis et al, 2007]. Additionally, a longitudinal study by Andersson et al [2001] showed that tinnitus maskability is an important prognostic factor for future tinnitus annoyance. This is illustrated by the fact that many patients are actively seeking sources of masking in their daily life to diminish tinnitus perception.…”
Section: Efficacymentioning
confidence: 70%
“…In previous clinical trials with the MML as the efficacy outcome variable, such a relationship has indeed been observed [Jastreboff et al, 1994;Davis et al, 2007]. Additionally, a longitudinal study by Andersson et al [2001] showed that tinnitus maskability is an important prognostic factor for future tinnitus annoyance. This is illustrated by the fact that many patients are actively seeking sources of masking in their daily life to diminish tinnitus perception.…”
Section: Efficacymentioning
confidence: 70%
“…Exposure to noise is responsible for the most common cause of tinnitus 37,38 , reported by about 25% of the individuals exposed to it 6,38 . In this series, tinnitus prevalence was of approximately 48%, much higher than the one reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They found that tinnitus distress might continue despite having tinnitus for 4.9 years, but that tolerance to tinnitus decreased. Much of the literature regarding treatment response to tinnitus indicates a lack of long-term outcomes except for those people that received cognitive behavioural therapy for tinnitus [59]. Therefore, despite treatment, …”
Section: Coping Stylesmentioning
confidence: 99%